Seismic performance of circular RC columns strengthened in flexure using NSM reinforcement and externally bonded BFRP sheets. (1st April 2022) - Zeng, Xinggui; Jiang, Shao-Fei; Deng, Kun; Huang, Haisheng; Cui, Erjiang
Highlights: The flexure of RC columns can be effectively enhanced by using NSM reinforcement. Seismic behavior of strengthened column is improved, but stiffness is not changed. The recoverability of all strengthened columns can be improved. Strengthening scheme of NSM BFRP bars and unidirectional BFRP sheets is optimal. BFRP as NSM material is more effective in increasing the recoverability of columns. Abstract: To study the seismic performance and recoverable capacity of reinforced concrete (RC) columns strengthened in flexure by employing different kinds of reinforcing materials, six 1/4.7 scale circular specimens including one control, which were strengthened by combining near-surface-mounted (NSM) reinforcement with externally bonded basalt fiber reinforced polymer (BFRP) sheets, were designed to investigate the seismic behavior and tested under the constant axial compressive load and lateral cyclic loading. The experimental parameters included different types of NSM reinforcing materials (carbon or basalt fiber reinforced polymers, steel), confinement conditions (no wrapping and wrapping), and different types of externally bonded BFRP sheets (unidirectional and bidirectional BFRP sheets). The results demonstrate that. the scheme of NSM reinforcement is an effective solution toward enhancing the flexural capacity and the recoverable performance of RC columns. Compared to the other strengthening schemes, the scheme (column C3-10B-4U) combining NSM BFRP bars with externally bonded BFRP unidirectional sheets is most effective in increasing the elastic energy dissipation capacities and also enhancing the ductility and deformation capacity of strengthened columns, but do not change the stiffness significantly. Furthermore, the results indicate that the residual displacement of the column C3-10B-4U is the smallest of all columns under the same applied displacement and thereby the recoverability of the column C3-10B-4U was better than that of the other strengthened columns.